Confinement of Reinforced-Concrete Columns with NonCode Compliant Confining Reinforcement plus Supplemental Pen-Binder - Kristianto, Anang; Imran, Iswandi; Suarjana, Made; Pane, Ivindra (Journal of Engineering and Technological Sciences, 2012)
Abstract.  One  of  the  important  requirements  for  earthquake  resistant  building related  to  confinement  is  the  use  of  seismic  hooks  in  the  hoop  or  confining reinforcement  of  reinforced-concrete  column  elements. However, installation of a  confining  reinforcement  with  a  135-degree  hook  is  not  easy.  Therefore,  in practice, many construction workers apply a confining reinforcement with a  90-degree  hook  (non-code  compliant).  Based  on  research  and  records  of  recent earthquakes  in  Indonesia,  the  use  of  a  non-code  compliant  confining reinforcement  for  concrete  columns  produces  structures  with  poor  seismic performance.  This paper  presents a study  that  introduces  an additional element that is expected to improve the effectiveness of concrete columns confined with a non-code compliant  confining reinforcement. The additional element, named a pen-binder,  is   used to keep the  non-code compliant  confining reinforcement in place. The effectiveness of this element  under pure axial concentric loading  was investigatedcomprehensively.The  specimens  tested  in  this  study  were  18 concrete columns,with a cross-section of 170 mm x 170 mm and a height of 480 mm. The main test variables were the material type of the  pen-binder, the angle of  the  hook,  and  the  confining  reinforcement  configuration.The  test  results indicate  that  adding  pen -binders  can  effectively  improve  the  strength  and ductility of the column specimens confined with a non-code compliant  confining reinforcement.